2022
DOI: 10.1128/spectrum.03415-22
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Cefditoren and N -acetyl- l -Cysteine Shows a Synergistic Effect against Multidrug-Resistant Streptococcus pneumoniae Biofilms

Abstract: Streptococcus pneumoniae is one of the deadliest bacterial pathogens, accounting for up to 2 million deaths annually prior to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Vaccines have decreased the burden of diseases produced by S. pneumoniae , but the rise of antibiotic-resistant strains and nonvaccine serotypes is worrisome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Other approaches to combat biofilms include utilising non-conventional agents in conjunction with antibiotics. Results of a study done by Llamosí et al 26 revealed that when an antioxidant N-acetyl-L-cysteine (NAC) was used in combination with cefditoren, a cephalosporin antibiotic, NAC significantly enhanced inhibition and eradication of MDR S. pneumoniae biofilms. Similarly, enhanced anti-biofilm effects were seen when nitric oxide was utilised synergistically with antibiotics.…”
Section: Enhancing Activity Of Conventional Antimicrobials Synergisti...mentioning
confidence: 99%
“…Other approaches to combat biofilms include utilising non-conventional agents in conjunction with antibiotics. Results of a study done by Llamosí et al 26 revealed that when an antioxidant N-acetyl-L-cysteine (NAC) was used in combination with cefditoren, a cephalosporin antibiotic, NAC significantly enhanced inhibition and eradication of MDR S. pneumoniae biofilms. Similarly, enhanced anti-biofilm effects were seen when nitric oxide was utilised synergistically with antibiotics.…”
Section: Enhancing Activity Of Conventional Antimicrobials Synergisti...mentioning
confidence: 99%
“…Propolis has antimicrobial activity against planktonic forms as well as an inhibitory effect on the biofilm production of Staphylococcus aureus (both methicillin-susceptible (MS) and methicillin-resistant (MR), Staphylococcus epidermidis, and Pseudomonas aeruginosa [15][16][17]. Both NAC and propolis showed synergistic effects with certain antibiotics when tested as a single compound (propolis with beta-lactam antibiotics and NAC with cephalosporin) demonstrating the ability to enhance their effects even against resistant strains, which is a promising and effective strategy against bacterial biofilms [18,19]. However, the synergistic effect of a fixed combination of NAC and dry propolis extract against bacterial biofilms has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%